(untitled) (Global Journal of Medical Research, 2019)
Introduction: Papillary thyroid carcinoma (PTC) is the most common malignant neoplasm of thyroid follicular epithelium. Its incidence has increased dramatically in past few decades reaching upto 80% of malignant thyroid tumors. Objectives: To assess the usefulness of the panel of immuno- histochemical markers #x2013; Cytokeratin 19 (CK19), Galectin 3 (GAL-3) and Hector Battifora mesothelial 1(HBME-1) in the prognostication of papillary thyroid carcinoma (PTC). Materials